Genomic recombination in primate bocavirus: inconsistency and alternative interpretations - Yee, Ling Chong; Kar, Hon Ng (Springer US, 2017)
Human bocavirus (HBoV) is a single-stranded DNA virus in Parvoviridae family, causing respiratory diseases in human. The recent identifications of genomic recombination among the four human bocavirus genotypes and related non-human primate bocaviruses have shed lights into the evolutionary processes underpinning the diversity of primate bocavirus. Among these reports, however, we found inconsistency and possible alternative interpretations of the recombination events. In this study, these recombination events were reviewed, and the related genome sequences were re-analysed, aiming to inform the research community of bocavirus with more consistent knowledge and comprehensive interpretations on the recombination history of primate bocavirus.